Berkarya Melalui Film: Pendampingan Pembuatan Film Pendek Bagi Siswa Madrasah Aliyah - Pratiwi, Rhesa Zuhriya Briyan; Eny Susilowati; Muhammad Thoriq Nuraviananda; Icha Imkasari Aulia Rahma; Sayyid Iksanudinoor Abdillah; Wisnu Sadana Nur Hutama (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The importance of the soft skills of high school students today tends to be a social concern. Judging from the development of digitalization of existing media, high school students need to prepare and equip themselves to face the rhythm of learning in higher education, or be ready to enter the community with all their competencies. The purpose of this service is to provide assistance for high school students and/or equivalent to Madrasah Aliyah (MA) in the process of making short films. The service is carried out in two stages and is located at MAN 1 Special Program (PK) Surakarta. Through this service, the participants were given material about the initial concept of making a short film, as well as a number of stages in making a short film. Then, participants were asked to practice some simple techniques in taking pictures on film, and continued with the process of making short films. Overall, the participants are expected to have the ability and knowledge of how to make a short film, starting from drafting concepts and story ideas, making scripts, the execution process in shooting, as well as editing and the final stage.